2000
DOI: 10.1080/014311600210146
|View full text |Cite
|
Sign up to set email alerts
|

Mapping land cover types in the Amazon Basin using 1 km JERS-1 mosaic

Abstract: In this paper, the 100 meter JERS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…These advanced techniques include using fully polarimetric SAR and texture analysis (Hoekman and Quiñones, 2002;Saatchi et al, 2007aSaatchi et al, , 2000, fusion of radar and optical sensors (Kellndorfer et al, 2010;Moghaddam et al, 2002), fusion of L-band and X-band radar (Englhart et al, 2011), or SAR Interferometry techniques (Treuhaft et al, 2004).…”
Section: Potential Of Alos-palsar To Estimate Agbmentioning
confidence: 99%
“…These advanced techniques include using fully polarimetric SAR and texture analysis (Hoekman and Quiñones, 2002;Saatchi et al, 2007aSaatchi et al, , 2000, fusion of radar and optical sensors (Kellndorfer et al, 2010;Moghaddam et al, 2002), fusion of L-band and X-band radar (Englhart et al, 2011), or SAR Interferometry techniques (Treuhaft et al, 2004).…”
Section: Potential Of Alos-palsar To Estimate Agbmentioning
confidence: 99%
“…Nevertheless, Landsat TM data can be used for qualitative evaluation and monitoring of forest regeneration, as has been recommended by the International Tropical Timber Organization (ITTO), using the forest canopy density technique (JOFCA, 1997). As an alternative tool, the use of active remote-sensing data, such as images collected using synthetic aperture radar (SAR), has been suggested for the evaluation of TAGB in forests, since variations in SAR measurements are related strongly to foliage and branch density, trunk biomass, and various structural aspects of forests (Le Toan et al, 1992;Foody et al, 1997;Luckman et al, 1998;Saatchi et al, 2000).…”
Section: Estimation Of Tagb From Canopy Heightsmentioning
confidence: 99%
“…Texture extraction algorithms have been developed from remotely sensed data for various spatial resolutions (Haralick et al, 1973;Haralick, 1979;Gong et al, 1992;Hassan and He 1995;Riou et al, 1997;Saatchi et al, 2000, Nyoungui et al, 2002Xu et al, 2003). All these studies demonstrated that texture in a local pixel neighborhood can be used to improve vegetation discrimination in highresolution images (Hudak et al, 1998;Podest and Saatchi, 2002).…”
Section: Introductionmentioning
confidence: 96%